OBAMATARE-Alquran: The Syntax of the Quran-Based CTL Model in the Learning of Islam Religious Education in Higher Education - Indah Muliati; Alfurqan Alfurqan; Murniyetti Murniyetti; Sulaiman Sulaiman (AL-ISHLAH: Jurnal Pendidikan, 2023)
Research on the CTL is based on many findings that most students have yet to be able to make connections between what they learn and its various uses in real life. This study aimed to develop an Alquran-based CTL model in the subject of Islamic Religious Education (PAI) in Higher Education, specifically on the syntax design of the Quran-based CTL model. This study used the RD method with the ADDIE model approach. The results of this study were the syntax of the Quran-based CTL model in PAI learning in Higher Education, which were summarized in the acronym OBAMATARE-Alquran, O: direct/orientate, BA: (baca) read Alquran, MA: (masalah) formulate a problem, TA: (tanya jawab) discussion, ask-answer-group/independent (solving problems)/guiding inquiry and displaying results, RE: reflection and evaluation. The syntax uses verses from Alquran relevant to the learning theme. OBAMATARE-Alquran, the Alquran-based CTL model, follows seven CTL activities. Constructivism, inquiry, question and answer and learning community activities could be seen in learning activities when students discussed in groups and investigated the details of the provided problems in LKM and picture/video shows. Then students found roots and problem solutions by exploring information. Students would exemplify ways to solve problems throughout the modelling step of solving problems. Reflections were done on the opening and closing activities. Meanwhile, evaluation in the form of authentic assessment was carried out during learning and at the end. This research is only limited to Alquran-based CTL syntax, requires further trials. This research can be developed in the form of learning modules, learning media and learning evaluation.